Antenatal Care Bed For Preeclamsi Early Detection Based on Web System - Ramadhan, Fiqih Fahrur; Pudji, Andjar; Mak’ruf, Muhammad Ridha; Misra, Shubhrojit (Jurusan Teknik Elektromedik, Politeknik Kesehatan Kemenkes Surabaya, Indonesia, 2023)
One of the causes of the high maternal mortality rate is dominated by three factors, one of which is preeclampsia. Preeclampsia is a condition in which the mother experiences hypertension and changes in BMI (Body Mass Index) at the 20th week of gestation. Preeclampsia indications in pregnant women are related to examinations, namely Antenatal care (ANC). Antenatal care is one of the prenatal checks with certain standards. Pregnant women need extra antenatal supervision from health workers. Preeclampsia detection carried out in health care facilities is currently considered to be still not optimal so that there are still many cases of preeclampsia that are not handled properly. A web-based ANC test is one of the ways that services for pregnant women may be improved. To make NIBP and BMI data supplied and received by IoT media helpful for the diagnostic procedure, this study will evaluate them. Knowing the reaction of NIBP and BMI data provided and received over IoT medium is the contribution of this research. The MPX5050 sensor and Loadcell, whose output will be processed and presented on a web page, will be used in the technique to accomplish this purpose. Although the largest error value was -5.4 at the measurement point of 150 mmHg at diastole, it can be argued that the measurement findings for the NIBP parameter are plausible. Overall NIBP measures, however can be considered practicable and can be used to human measurements. Additionally, the weight parameter measurement data have an error value of 0.19328%. From this study, it can be inferred that transmitting IoT-based NIBP and BMI data has an impact on received lost data or delays. The findings from this study are expected to be developed in further research.